Quantitative analysis and documentation of women’s ethnomedical knowledge in Western West Bengal, India - Mondal, Manishree; Sau, Arup Kumar; Das, Swastik; Karmakar, Puja (Ethnobotany Research and Applications, 2025)
Background: Indigenous women in every tribal society of “Jangalmahal” area of Western West Bengal are truly accredited for restoration, transmission and preservation of their ethnomedicinal knowledge like ethnomedical men but their knowledge is not yet recognized and documented for their holistic use, evaluation and validation. This research focuses on the knowledge and perception of ethnomedicinal plants and indigenous therapeutic practices of common indigenous women and women traditional healers. Methods: A cross-sectional survey was executed among 400 tribal women and 10 women ethnomedical healers in 10 remote forest villages selected by stratified random sampling procedure of Western West Bengal. The women healers mainly identify the medicinal plants and provide the information about importance, plant parts used, mode of administration of medicines, preferred medicinal plants. The tribal women respondents provide the information about the effectiveness of these medicines and validation of the knowledge provided by the ethnomedicinal women healers. A semi-structured and open-ended questionnaire schedule was employed for calculation of descriptive statistical techniques like CPP, ICF, FL, UV, IV, CSI, PCC. Results: Altogether 60 plant species of 34 families have been identified by women traditional healers used for 38 ethnomedicinal preparations for curing 22 types of diseases. Women healers mostly practice oral administration of ethnomedicines (72%). Multiple medicinal plants were cited against particular ailments, and mixing of two or more different medicinal plants (38%) against a single ailment was reported. Conclusions: The documented ethnomedicinal knowledge of the common indigenous women and women healers from this study can be used to support the country’s primary health care system of human and livestock. It will be helpful in future studies to validate bioactivity of selected medicinal plants as well as to increase their acceptability in health care systems both nationally and internationally. Keywords: Indigenous women, Jangalmahal, Ethnomedicinal plants, Therapeutic practices, Stratified random sampling, Descriptive statistics Women traditional healers, Diseases, Ethnomedicine, Health care.